Effect of Exogenic Proteolytic Enzymes on Transfer of Plasmid Genes in Mixed Bacterial Biofilms - G. V. Tets; N. K. Artemenko; N. V. Zaslavskaya; K. L. Artemenko; G. YU. Knorring; V. V. Tets; YU. I. Sternin (Антибиотики и Химиотерапия)
The effect of the enzyme complex from Vobenzin on transfer of plasmid genes In biofilms of gramnegative bacteria was studied. The extracellular matrix of the bacterial biofilms was shown to contain extracellular DNA carrying the antibiotic resistance markers. The action of the enzyme complex resulted in lower frequency of the antibiotic resistance genes transfer in mixed bacterial biofilms.